Inspection of GTI Bridge in Kampung Makassar Timur Urban Village - Muhammad Usamah; Joni Hermanto; Andri Wandra (BIOSAINSTEK, 2025)
Bridges are vital infrastructure that play a crucial role in supporting community mobility and logistics distribution. Regular inspections are essential to ensure the safety and operational feasibility of these structures. This study aims to evaluate the physical and structural condition of the GTI Bridge located in Kampung Makassar Timur. The inspection methods employed include visual assessment, structural dimension measurements, and evaluatpion of key elements such as the bridge deck, support beams, columns, and joints. The inspection results indicate minor to moderate damage in several structural components, including hairline cracks on concrete surfaces, corrosion on steel elements, and deterioration of protective coatings. Based on the analysis, the bridge is deemed serviceable, provided that routine maintenance and repairs are carried out on the affected parts. Maintenance and repair recommendations have been formulated to extend the service life of the bridge and prevent potential safety hazards in the future.